2017
DOI: 10.1007/s10551-017-3625-0
|View full text |Cite
|
Sign up to set email alerts
|

An Identity Perspective on Ethical Leadership to Explain Organizational Citizenship Behavior: The Interplay of Follower Moral Identity and Leader Group Prototypicality

Abstract: Despite the proliferation of research on ethical leadership, there remains a limited understanding of how specifically the assumingly moral component of this leadership style affects employee behavior. Taking an identity perspective, we integrate the ethical leadership literature with research on the dynamics of the moral self-concept to posit that ethical leadership will foster a sense of moral identity among employees, which then inspires followers to adopt more ethical actions, such as increased organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(159 citation statements)
references
References 103 publications
(142 reference statements)
12
124
2
3
Order By: Relevance
“…Extending the current research state, the present study first examined the moderating function of follower moral identity as a self-concept based personality variable, thus adding further insight in the followers' active role in the ethical leadership process. Coincidently, our findings contradict the results of several studies that detected the effects of ethical leadership on an employee's moral identity (Wen and Chen, 2016 ; Gerpott et al, 2017 ; Bavik et al, 2018 ), as ethical leadership and moral identity were unrelated in both of our studies, but they exhibited an interaction effect. Thus, the present studies add a new perspective on the relationship between ethical leadership and follower moral identity.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Extending the current research state, the present study first examined the moderating function of follower moral identity as a self-concept based personality variable, thus adding further insight in the followers' active role in the ethical leadership process. Coincidently, our findings contradict the results of several studies that detected the effects of ethical leadership on an employee's moral identity (Wen and Chen, 2016 ; Gerpott et al, 2017 ; Bavik et al, 2018 ), as ethical leadership and moral identity were unrelated in both of our studies, but they exhibited an interaction effect. Thus, the present studies add a new perspective on the relationship between ethical leadership and follower moral identity.…”
Section: Discussioncontrasting
confidence: 93%
“…The role of a leader's moral identity with respect to the emergence of ethical leadership behavior has been confirmed (e.g., Mayer et al, 2012 ). Furthermore, several studies indicate that ethical leadership enhances an employee's moral identity (Wen and Chen, 2016 ; Gerpott et al, 2017 ; Bavik et al, 2018 ). However, the function of an employee's moral identity in the processing of ethical leadership behavior related to the evolution of follower outcomes has not been explored to date.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…For instance, sharing information about oneself and being forthright in their communications with employees should lead to greater perceived relational transparency. Similarly, Gerpott, Van Quaquebeke, Schlamp, andVoelpel (2019, p. 1073) suggested that interactive workshops focused on defining norms and values could serve the dual purpose of "helping leaders understand how to position themselves as more group prototypical and helping group members realize the more group prototypical aspects of their leaders." In addition, the metacognition literature highlights other strategies for impacting evaluative certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Because prototypical leader are seen as trusted source of information, prototypical leaders can reduce the uncertainty of subordinates regarding organizational identity so that subordinates are more confident to provide support (Hohman, Gaffney, & Hogg, 2017). Besides, prototypical leaders are considered to represent the characteristics of the organization, so that support and morale from subordinates will also upsurge because they are led by people who have similarities with their organization (Gerpott, Van Quaquebeke, Schlamp, & Voelpel, 2019).…”
Section: Resultsmentioning
confidence: 99%